Field notes contributed by Charles Fuller, fall 1987 - Fuller, Charleset al (1987)
Fall report of birds found in southeast Iowa contributed by Charles Fuller. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1987. Epson - sheet feed